PANDANGAN MANG KOKO DALAM BERKESENIAN - Tardi Ruswandi (LP2M ISBI Bandung, 2017)
This study focused Mang Koko in view ofthe arts in general, the artist, and the Sundanese karawitan. Mang Koko view of the matters that will be discussed in further description. The purpose is to explain Mang Koko view of the arts and artists. The method used is a qualitative method. While the results of this study revealed that the views Mang Koko the arts in general, because the art is an ancestral cultural heritage that should be maintained and developed. In everyday life the artist is not enough just good practice, but also to be godly, because the artist must have the mental strength, discipline, honesty, and can avoid the things that are negative. Similarly Sundanese gamelan, is not only an essential element in kahidupan artist, but should be part ofhuman life.